KETAHANAN KELUARGA NELAYAN PADA MASA PANDEMI COVID-19 - Surur, Saefi Fatikhu (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
This study aims to examine the specific changes that occurred in fishing families when hit by the pandemic covid-19. Also to understand in depth the meaning of a family and their efforts to maintain family harmony amidst the pandemic covid-19 outbreak. In general, the people of Pangandaran Regency live in the seacoast area, so that the majority of the people work as fishermen. When Large-Scale Restrictions (PSBB) were imposed, fishermen's families in Pangandaran district had to stop their activities. The method used is a qualitative study that is descriptive analytic with analysis tools of family resilience theory and functional structure theory. In the initial research, there were interesting findings, fishing families in Pangandaran Regency had quite varied efforts to maintain harmony and there were several changes in the roles and functions of family members in implementing these efforts.